Inspection of aluminum alloys by a multi-frequency eddy current method; Defence Technology; Vol. 11, iss. 2 - Egorov A. V.; Polyakov V. V.; Salita D. S.; Psakhie S. G. Sergey Grigorievich; Kolubaev E. A.; Chernyavskii A. G.; Vorobei I. V. (2015, 2015)
Title screen